2012
DOI: 10.1002/meet.14504901202
|View full text |Cite
|
Sign up to set email alerts
|

The notion of relevance in teacher information behavior

Abstract: Educators use information to support their teaching, which is largely concerned with the transfer of information. To support this information exchange, teachers manage complex information environments that are continually changing based on outside influences. Decisions on when to go out and seek additional information, what information to incorporate, and what information to dispose of are all based on notions of relevance. This exploratory study found that notions of relevance are largely driven by the educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…At her present school Vera regretted that collective work did not focus on courses. The choice of the textbook had been collective, and this is in line with the results obtained by Diekema and Whitney Olsen (2012), who observed that advice given by colleagues was the first reason for the adoption of a new resource by teachers. Vera complained about having no opportunity to ask questions, such as: ''And you, how do you teach such and such a notion ….''…”
Section: Vera's Collective Activities: Conditions For Collaborationsupporting
confidence: 76%
“…At her present school Vera regretted that collective work did not focus on courses. The choice of the textbook had been collective, and this is in line with the results obtained by Diekema and Whitney Olsen (2012), who observed that advice given by colleagues was the first reason for the adoption of a new resource by teachers. Vera complained about having no opportunity to ask questions, such as: ''And you, how do you teach such and such a notion ….''…”
Section: Vera's Collective Activities: Conditions For Collaborationsupporting
confidence: 76%
“…Initially, responses to the interview questions were analyzed for PIM‐ and information‐related features using thematic analysis (Boyatzis, ). This analysis was carried out on a subset of the data for PIM features and all the data for information features and provided input for two conference papers (Diekema & Olsen, , ). Informed by these themes and a literature review on teacher information behavior, an initial codebook was created for the in‐depth analysis of all the data.…”
Section: Methodsmentioning
confidence: 99%
“…A lot of sharing also went on informally. Materials from close colleagues were more likely to be relevant, as they deal with the same school and student population (Diekema & Olsen, 2012). It appears that sharing is more widespread among teachers than the 40 mechanical engineers in a study by Hicks, Dong, Palmer, and Mcalpine (2008), who found that a majority of their participants (60%) shared digital information with colleagues.…”
Section: Finding Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with this level of understanding, teachers have been reported to have difficulty finding, accessing and managing the information needed for instructional purposes (Khoo, 2006;Mardis, 2009;Mardis et al, 2012;Recker et al, 2005) and, therefore, regularly frustrated when seeking digital resources, leading to declined confidence (Barker, 2009;Common Sense Media, 2013;Mardis et al, 2012;Perrault, 2007aPerrault, , 2007b. Considering the confidence of educators in locating and selecting digital resources directly influences future selection and use of resources for instructional purposes (Mardis et al, 2012;Sappey and Relf, 2010), teachers have subsequently reduced their opportunities to enhance information skills to locate educational resources (Barker, 2010;Common Sense Media, 2013;Diekema and Olsen, 2012;Duke and Ward, 2009;Mardis, 2009;Perrault, 2007aPerrault, , 2007b causing further feelings of being overwhelmed (Barker, 2010;Mardis et al, 2012;Maull et al, 2010;Perrault, 2007b;Pattuelli, 2008). Such findings of prior studies potentially indicate that systems are not designed from the outset around the information needs, tasks and interactive approaches for effectively finding digital information (Barker, 2010;Common Sense Media, 2013;Guzey and Roehrig, 2009;Park, 2010;Perrault, 2007a).…”
Section: Users and Uses Of Video In Educationmentioning
confidence: 99%